Toleransi Tanpa Batas: Outlook Agamawan dan Kebijakan Migrasi Suku Batak Kristen ke Pedalaman Duri Bengkalis - Hamdan Daulay (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2019)
This study explores the concept of policy that needs to be implemented by the government in counteracting of religious intolerance. Based on the factors of population equality and economic prosperity, the government must be regarding the socio-religious aspect of the migration program in the interior of Duri Bengkalis, Riau. In order to realize the ideals of national social development, the portrait of the process of migrating Christian Bataks’ to the interior of Duri must be an outlook for the social conflicts that occur. Highlighting the case of intolerance between Christian Bataks’ and Malay Muslim tribes Duri is important to be contextually examined through a research approach. As a literacy for developing unlimited tolerance in the frame of pluralism, it is very appropriate if this study is analyzed using the perspective of the sociology of development. The process of developing through a migration program, I take field data through qualitative research. The data source was taken directly to the informant with the snowball sampling technique. After the data were analyzed by the process of data reduction, data display, and conclusion, I found that government policy was not optimal in accommodating the migration program. There are still occur caused by the inferior of people for the meaning of pluralism. Although in general, the community has lived up to the philosophy of Pancasila, these implications are lowly in everyday life. Efforts to reduce conflicts that occur in Bengkalis, the government needs to develop a roadmap for policies on religious dialogue. Religious harmony is very important. It is impossible to realize tolerance without limits if the supporting instruments are not a priority agenda. Especially in areas prone to an inter-religious conflict which are actually caused by economic disparity and political oligarchy.Studi ini bertujuan menjelaskan tentang konsep kebijakan yang perlu diterapkan oleh pemerintah dalam menangkal intoleransi beragama. Selain faktor pemerataan penduduk dan kesejahteraan ekonomi, penting kiranya pemerintah memperhatikan aspek sosialkeagamaan atas kasus migrasi yang terjadi di pedalaman Duri Bengkalis, Riau. Agar cita-cita pembangunan sosial secara nasional dapat terwujud, potret proses migrasi suku Batak Kristen ke pedalaman Duri harus menjadi outlook dalam menyusun kebijakan tanpa menimbulkan konflik sosial. Menyoroti kasus intoleransi antara suku Batak Kristen dan Muslim Melayu Duri menjadi penting untuk ditelaah secara kontekstual melalui pendekatan riset. Sebagai acuan mengembangkan toleransi tanpa batas dalam bingkai pluralisme, kajian ini dianalisis menggunakan perspektif sosiologi pembangunan. Proses pembangunan bangsa melalui program migrasi, penulis mengambil data lapangan melalui penelitian kualitatif. Sumber data diambil langsung kepada informan dengan teknik snowball sampling. Setelah data dianalisis dengan proses reduksi data, display data, dan penarikan kesimpulan, penulis menemukan belum optimalnya kebijakan pemerintah dalam mengakomodir program migrasi. Hal utama yang menjadi pemicunya adalah masih rendahnya masyarakat memahami makna pluralisme. Walaupun secara umum masyarakat sudah menghayati falsafah Pancasila, tetapi masih rendahnya implikasi tersebut dalam kehidupan sehari-hari. Upaya meredam konflik yang terjadi di Bengkalis, pemerintah perlu menyusun roadmap kebijakan tentang dialog agama. Kerukunan agama sangat penting ditegakkan. Mustahil dapat mewujudkan sikap toleransi tanpa batas jika instrumen pendukungnya bukan menjadi agenda prioritas. Terutama di daerah-daerah yang rawan konflik antar umat beragama yang sejatinya disebabkan oleh faktor kesenjangan ekonomi dan oligarki politik.